Effect of Different Rootstocks on Growth and Leaf Nitrogen in Young Citrus Cultivars - HASSABALLA, ISSAM A.; FAHMY, IBRAHIM (The Libyan Journal of Agriculture, 2023)
In this preliminary report, bud-take, growth measurements and leaf nitrogen level in young citrus rootstock seedlings and their combinations with ‘Washington’ navel, ‘Valencia’ and ‘Hamlin’ oranges, ‘Clementine’ mandarin and ‘Prior Lisbon’ lemon as tops were compared. All cultivars on rough lemon gave the highest bud-take. ‘Prior Lisbon’ lemon scored the highest success of bud-union regardless of the stock. Among the five rootstocks studied, rough lemon followed by ‘Rangpur’ lime induced the most vigorous scion growth. By the end of the second year in the field, the ‘Clementine’ on ‘Cleopatra’ mandarin was the only superior combination in growth when compared with the sour orange stock. In general, ‘Troyer’ citrange was the least vigorous in all combinations. Leaf nitrogen level was highest in two-year-old nursery grown budlings of ‘Hamlin’ orange on ‘Rangpur’ lime and ‘Valencia’ orange on rough lemon among all nine orange combinations. This was also true for the ‘Prior Lisbon’ on ‘Rangpur’ lime.